2019
DOI: 10.1155/2019/7530480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Molecular State of Piperine in Cyclodextrin Complexes by Near-Infrared Spectroscopy and Solid-State Fluorescence Measurements

Abstract: The purpose of this study was to evaluate the physicochemical properties of piperine (PP) in ground mixtures (GMs) of PP with α-, β-, or γ-cyclodextrin (CD) under conditions of humidity, heat, and humidity-heat. In solid-state fluorescence measurements, the fluorescence maxima for GM (PP/αCD = 1/2), GM (PP/βCD = 1/1), and GM (PP/γCD = 1/1) were observed at 463, 472, and 469 nm, respectively. On the other hand, the humidified GMs exhibited maxima at 454, 460, and 465 nm, while the humidified-heated samples disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“… 15 NIR and solid-state fluorescence measurements revealed that the molecular behavior of PP inside the α, β, and γCD cavities changed by water and heat factors depends on the mobility of the methylenedioxyphenyl group. 16 Also, from a Raman spectroscopy measurement, PP/αCD, PP/βCD, and PP/γCD inclusion complexes prepared by the GM method have been confirmed to suppress the motility of the methylenedioxyphenyl group and pentadiene chain that are hydrophobic parts of PP. 17 From these reports, it is important to evaluate the carbon–carbon bonds of PP to understand the intermolecular interaction with CD.…”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… 15 NIR and solid-state fluorescence measurements revealed that the molecular behavior of PP inside the α, β, and γCD cavities changed by water and heat factors depends on the mobility of the methylenedioxyphenyl group. 16 Also, from a Raman spectroscopy measurement, PP/αCD, PP/βCD, and PP/γCD inclusion complexes prepared by the GM method have been confirmed to suppress the motility of the methylenedioxyphenyl group and pentadiene chain that are hydrophobic parts of PP. 17 From these reports, it is important to evaluate the carbon–carbon bonds of PP to understand the intermolecular interaction with CD.…”
Section: Results and Discussionmentioning
confidence: 87%
“… 25 Also, the stability constant values of PP/αCD were reported to be K α1/1 = 7473 M –1 and K α1/2 = 47 M –1 . 16 Since the stability constant ( K α1/2 ) of PP/αCD = 1/2 showed a low value, the dissociated αCD forms an inclusion complex with lecithin. As a result, the proportion of PP/αCD = 1/1 inclusion complex increased leading to the higher solubility of PP.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There are at least two types of inclusion complex formulations: binary inclusion complexes (BIC) which consist of piperine and a complexing agent, and ternary inclusion complexes (TIC), a supramolecular stable system which consists of a little amount of auxiliary component in a form of hydrophilic polymer in addition to BIC, and has proven its superiority in enhancing drug solubility compared to BIC [41][42][43]. Piperine BIC formation using cyclodextrins (CD) along with derivatives such as ethylenediamineβ-CD (EN-β-CD) and hydroxypropyl-β-CD (HP-β-CD) have succeeded in increasing solubility, dissolution rate, intestinal absorption, bioavailability, bioaccessibility, and bioactivity [42][43][44][45][46][47][48]. Particle size did not have a role in solubility improvement.…”
Section: Inclusion Complexesmentioning
confidence: 99%
“…The dissolution medium was maintained at 37 ± 0.5 °C. The samples of dissolution medium (10 ml) were withdrawn at specified time intervals (2,4,6,8,10,15,30,45 and 60 min). The concentration of atenolol in the samples of the dissolution medium was analyzed using UV-visible, double beam spectrophotometer (Shimadzu UV-1800) at λ 274 nm.…”
Section: Dissolution Test Of Atenolol-β-cyclodextrin Inclusion Complexmentioning
confidence: 99%
“…dispersion, salt formation, co-crystal, inclusion complex, etc. 4,5 Inclusion complex is one of the approaches which has been used in the pharmaceutical field to improve the dissolution of poorly soluble drugs, taste masking of bitter drugs, and enhance the stability of several drugs 6,7 . Cyclodextrins are commonly used in the inclusion complex system because of its structure.…”
mentioning
confidence: 99%